PERAN BADAN USAHA MILIK DESA (BUMDes) SUKOSARI MAKMUR DALAM PENGELOLAAN WISATA POETOEK SOEKO DI DESA SUKOSARI KECAMATAN TRAWAS KABUPATEN MOJOKERTO - Tria Maulana Zhara; Deby Febriyan Eprilianto; Galih Wahyu Pradana; Melda Fadiyah Hidayat (Publika, 2026)
The development of village tourism is a form of utilizing village potential that requires sustainable management. The existence of Poetoek Soeko Tourism provides economic and social benefits for Sukosari Village. However, various obstacles are still encountered in its management, particularly in the implementation of the role of BUMDes. Therefore, this study aims to analyze the role of BUMDes Sukosari Makmur in managing Poetoek Soeko Tourism. The research uses a qualitative approach with descriptive method, employing the theory of roles according to Munir (in Nilawati et al., 2021), which consists of the roles of entrepreneur, coordinator, and facilitator. Data collection techniques were carried out through interviews, observations, and documentation. The results show that BUMDes Sukosari Makmur has performed its roles as an entrepreneur, coordinator, and facilitator in tourism management. The entrepreneur role provides economic and social benefits to the village, such as contributions to Village Original Income and job provision, but it is not yet optimal, especially in terms of tourism attraction innovation. The coordinator role has been implemented through coordination with the village government, employees, and community, but it is still limited to the planning and asset handover stages, with low community participation and no cooperation with external parties. There are still poorly maintained facilities, and tourism promotion has not been effective. Meanwhile, the facilitator role is demonstrated through the provision of tourism facilities, services, and support for community activities, but it still faces challenges such as limited staff numbers, the sustainability of human resource training. Based on these findings, strengthening the role of BUMDes is needed in innovation, continuous coordination, improving human resource capacity, and more planned promotional strategies so that the management of Poetoek Soeko Tourism can run effectively and sustainably.